Aplikasi Health Promotion Model sebagai Upaya Penanggulangan Penderita Tuberkulosis di Desa Punggur Kapuas Kecamatan Sungai Kakap Kabupaten Kubu Raya Kalimantan Barat - Nita Arisanti Yulanda; Muhammad Ali Maulana; Djoko Priyono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Lung tuberculosis is a contagious infectious disease caused by Mycobacterium tuberculosis (TB) and often manifests in the lungs. This community service is motivated by the high number of cases of BTA (+) Tuberculosis in the Kubu Raya Regency. The purpose of this community service as an effort to provide health education as a form of application of existing nursing theories, namely the Health Promotion Model, which views the importance of health promotion and disease prevention is something that is logical and economical in Punggur Kapuas Village, West Kalimantan. The service method used first is the TB patient survey to identify smear through the sputum of people who are at risk of TB by conducting home visit checks, the second is counseling about TB, and the third is a demonstration of cough ethics and TB Kit for patients and families to reduce the risk of TB transmission. The community service activity was attended by 50 residents of the Kapuas Punggur Village. This activity also provided TB kit media containing masks, alcohol spray, sputum pots that can be used when TB sufferers want to get rid of sputum so that they are not disposed of anywhere, a small medicine box that can remind TB sufferers to take medicine. The results of this activity obtained an increase in the knowledge of residents about TB prevention before providing health education by 27 (54%) to 35 (70%) residents who have sufficient knowledge.